GE_GERICHTE P/3185/2020 vom 28. November 2024 - GE Cour de justice (2024)
VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION;VIOLATION DE DOMICILE;VIOLENCE DOMESTIQUE;TRAITEMENT AMBULATOIRE | CP.63; CP.186; CP.219